The role of skin testing, drug challenge and IFN-γ ELISpot in delayed hypersensitivity to iodinated contrast media - Ana Maria Copaescu; Kyra Y. L. Chua; Effie Mouhtouris; Natasha E. Holmes; Moneerah AlGassim; Ibtihal Al Otaibi; Florian Stehlin; Ghislaine A. C. Isabwe; Christos Tsoukas; Jean-Francois Toupin; Derek Lee; Moshe Ben-Shoshan; et al. (Allergy, Asthma & Clinical Immunology)
Abstract Background The use of in vivo and ex vivo diagnostic tools for delayed hypersensitivity reactions (DHRs) associated with iodinated contrast media (ICM) is currently ill-defined. Objective To evaluate the role of in vivo and ex vivo diagnostic tools for DHRs occurring >6 h following intravenous low-osmolality ICM. Methods We conducted a prospective, multicenter, international cohort study. The patients were recruited from two tertiary care adult allergy clinics, Austin Health, Australia and the McGill University Health Centre, Canada. Eligible participants were adults who reported a DHR after receiving ICM. In vivo testing (skin testing and intravenous challenge) was performed to identify an alternative agent. Ex vivo testing using interferon-γ enzyme-linked ImmunoSpot assay was performed in four Australian patients to explore its diagnostic performance. Results The culprit ICM was identified by dIDT in 17/20 (85%) while in 3/20 (15%) a challenge was necessary to confirm delayed hypersensitivity. All patients with a positive dIDT to iohexol were positive to iodixanol (15/15; 100%) while 3/4 (75%), 3/4 (75%), 4/6 (67%), and 3/5 (60%) were positive to iopromide, ioversol, iopamidol, and iobitridol, respectively. Overall, 7/20 (35%) patients tolerated a challenge with an alternative ICM. The IFN-γ release assay was negative for the implicated ICM in 4 patients with confirmed DHR through a positive dIDT. Conclusion dIDT allowed confirmation of T cell-mediated allergy to the implicated ICM in 85% of patients with a strong clinical suspicion of DHR and identification of non-cross-reactive ICM in 35% of patients. The IFN-y ELISpot was not useful in the four patients tested.